Affective Privilege: Asymmetric Interference by Emotional Distracters - Reeck, Crystal; Egner, Tobias (Frontiers in Psychology, 2011)
Numerous theories posit that affectively salient stimuli are privileged in their capacity to capture attention and disrupt ongoing cognition. Two underlying assumptions in this theoretical position are that the potency of affective stimuli transcends task boundaries (i.e., emotional distracters do not have to belong to a current task-set to disrupt processing) and that there is an asymmetry between emotional and cognitive processing (i.e., emotional distracters disrupt cognitive processing, but not vice versa). These assumptions have remained largely untested, as common experimental probes of emotion-cognition interaction rarely manipulate task-relevance and only examine one side of the presumed asymmetry of interference. To test these propositions directly, a face-word Stroop protocol was adapted to independently manipulate (a) the congruency between target and distracter stimulus features, (b) the affective salience of distracter features, and (c) the task-relevance of emotional compared to non-emotional target features. A three-way interaction revealed interdependent effects of distracter relevance, congruence, and affective salience. Compared to task-irrelevant distracters, task-relevant congruent distracters facilitated performance and task-relevant incongruent distracters impaired performance, but the latter effect depended on the nature of the target feature and task. Specifically, task-irrelevant emotional distracters resulted in equivalent performance costs as task-relevant non-emotional distracters, whereas task-irrelevant non-emotional distracters did not produce performance costs comparable to those generated by task-relevant emotional distracters. These results document asymmetric cross-task interference effects for affectively salient stimuli, supporting the notion of affective prioritization in human information processing.